1996
DOI: 10.1007/bf00019480
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a cDNA encoding a Rab1-like small GTP-binding protein from Petunia hybrida

Abstract: The cloning of small GTP-binding proteins from Petunia hybrida was performed using a PCR-based strategy. Degenerate primers were designed from the DTAGQE and FMETSA consensus sequences. Three different cDNAs were amplified. The deduced polypeptide sequences PhPCRGP1 and PhPCRGP2 were homologous to RB11_HUMAN and PhPCRGP3 to RAB1A_HUMAN. Using PhPCRGP3 as a probe, 8 identical clones were selected from a Petunia leaf cDNA library. They all encode the same 22.5 kDa polypeptide, PhRAB1, able to bind GTP in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A large family of GTPases, the Rab family proteins, regulates the specificity and vesicle trafficking (Bischoff et al, 1999). Elevated expression of several Rab proteins was found in rapidly growing cells or in cells requiring active membrane biogenesis, such as germinating pollen or flower tissue in Petunia hybrida (PhRAb1), Z. mays (ZmRAB1a, ZmRAB1b, ZmRAB1c) and A. thaliana (AtRAB2a) (Jako and Teyssendier De La Serve, 1996;Palme et al, 1992Palme et al, , 1993. Szumlanski and Nielsen (2009) have reported that AtRABA4D is specifically expressed in pollen.…”
Section: Genes Specifically Expressed In the Male Thallimentioning
confidence: 98%
“…A large family of GTPases, the Rab family proteins, regulates the specificity and vesicle trafficking (Bischoff et al, 1999). Elevated expression of several Rab proteins was found in rapidly growing cells or in cells requiring active membrane biogenesis, such as germinating pollen or flower tissue in Petunia hybrida (PhRAb1), Z. mays (ZmRAB1a, ZmRAB1b, ZmRAB1c) and A. thaliana (AtRAB2a) (Jako and Teyssendier De La Serve, 1996;Palme et al, 1992Palme et al, , 1993. Szumlanski and Nielsen (2009) have reported that AtRABA4D is specifically expressed in pollen.…”
Section: Genes Specifically Expressed In the Male Thallimentioning
confidence: 98%
“…Interestingly, VcRab1 (formerly YptV1) protein levels did not change throughout the whole life cycle of V. carteri [120]. Elevated expression levels were found in rapidly growing cells or in cells requiring active membrane biogenesis, such as germinating pollen or flower tisssue where PhRab1, ZmRab1a, ZmRab1b, ZmRab1c and AtRab2a genes were highly expressed [118,121,122]. Using a promoter-GUS fusion, the AtRab2a gene was shown to be transcribed in maturing pollen which accumulate ER and Golgi membranes to sustain pollen tube growth after germination [123].…”
Section: Rab1 and Rab2 Controlling The Er -Golgi Trafficmentioning
confidence: 99%
“…The ERto-Golgi pathway is thought to be particularly important to cells that must undergo rapid growth and/or membrane biogenesis (Driouich et al 1993;Hawes et al 1995). Elevated expression levels of Rab1 and Rab2 were found in germinating pollen, seedlings or Xower tissues where, ZmRab1a,b,c, AtRab2a and PhRab1 genes were highly expressed (Palme et al 1992(Palme et al , 1993Jako et al 1996).…”
Section: Discussionmentioning
confidence: 99%